Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - Chapters 1-2 Cumulative Review Problem Set - Page 91: 17



Work Step by Step

First, we simplify the expression by combining like terms: $-7x+4y+6x-9y+x-y$ =$(-7x+6x+x)+(4y-9y-y)$ =$(-x+x)+(-5y-y)$ =$0+(-6y)$ =$-6y$ Now, we substitute $y=0.4$ into the expression: $-6y=-6(0.4)=-6\times\frac{4}{10}=-\frac{24}{10}=-2.4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.